Ultrasonographic diagnosis of intestinal intussusception caused by gastrointestinal stromal tumor in a canine: case report (Research, Society and Development, 2022)
In the small animal clinic, gastrointestinal diseases are frequent, especially considering the obstructive conditions in which they are seen as surgical emergencies. Among these, intestinal intussusception is a significant disorder, where a portion of the intestine invaginates into the lumen of the adjacent portion. Physical and ultrasound examination are important tools for diagnosis, with US being a safe, sensitive, specific and highly accurate diagnosis, thus avoiding false negatives. The objective of this study is to describe the case of a male canine diagnosed by ultrasound with acute intestinal intussusception caused by a surgically visualized gastrointestinal stromal tumor, aiming to emphasize the importance of such an examination for the disease and diagnosis. Also, primary TGI neoplasms refer to about 2% of canine neoplasms, with GIST being a rare type of neoplasia observed in this specie.